Peningkatan Literasi Siswa Melalui Workshop Public Speaking dan Leadership di Desa Wuakerong, Kecamatan Nagawutung, Kabupaten Lembata - Melani Armelya; Rosina Fitri Hartati; Fridorio Irfan Adhiputra Amol; Guntramus Nurak; Yohana Fransiska medho; Kristianus Simon H. Molan; Serli Stefania Binsasi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The public speaking and leadership workshop conducted for SDI 1 Loang students aims to enhance literacy and social skills, particularly in public speaking and leadership. The choice of this topic is highly relevant, as public speaking and leadership skills are crucial elements for personal and social development in today's global era. The community service method used included a participatory approach with interactive activities such as group discussions, simulations, and practical exercises designed to stimulate active student participation. The results of this workshop showed a significant improvement in students' communication skills, confidence, leadership abilities, and teamwork capabilities. This positive impact indicates that students are not only more confident in public speaking but also better at taking initiative in group situations. In conclusion, the training successfully enhanced students' competencies in public speaking and leadership. However, continuous support from schools and communities is essential to further facilitate the development of these skills, ensuring students are well-prepared to face future challenges.